Perfil das gestantes vivendo com HIV em tratamento antirretroviral no Brasil: coorte retrospectiva (2014-2019). - Solange Cristina Teixeira de Lima (2023)
In Brazil, cases of HIV in women occur mainly in the reproductive phase. The diagnosis occurs mainly during prenatal care, and even during pregnancy this diagnosis is sometimes delayed. Despite advances, this scenario brings challenges to public policies aimed at maternal and child health. In recent years, the virus detection rate in pregnant women in Brazil has shown an upward trend. Furthermore, there were changes in therapeutic protocols, related to the combination of therapeutic classes of antiretrovirals (ARV) and the criteria for starting antiretroviral therapy (ART) for pregnant women living with HIV (PWLHIV) in Brazil. The objective of this study was to evaluate the profile of PWLHIV on ART from 2014 to 2019 in Brazil. This is a descriptive and analytical retrospective cohort study conducted with national database data from the Medication Logistic Control System (SICLOM). Women aged 14 years or older, with at least one ARV dispensation in the pregnant category in SICLOM, during the study period, were included. Pregnant women were stratified into two categories: pregnant women who had previously used ART and pregnant women who started ART during pregnancy and were described according to sociodemographic variables and related to ART. A total of 34,659 pregnant women were included, of which 18,486 had previously used ART and 16,173 started ART during pregnancy. The results show that 32.6% of the pregnant women were aged between 30 and 39 years old, 46.7% were non-white, 38.5% had no partner, 27.7% had an education level between 8 and 11 years. Most (34.6%) were from the Southeast region. The average time of ART use was 174.2 days, and there was a record of adverse drug reaction (ADR) by 14.3% of the participants. During the study period, there were 39,019 pregnancies, with an average of 1.13 pregnancies per woman. The main ARV regimens used were lopinavir+ritonavir/zidovudine+lamivudine, between the years 2014 to 2016, tenofovir+lamivudine+efavirenz, in 2017, and tenofovir+lamivudine/raltegravir between 2018 and 2019. This study provides important information about the characteristics of PWLHIV and about the ARV regimens used in the treatment of HIV. The findings can contribute to support public policies that improve health care for PWLHIV.